Characterization of the complete chloroplast genome of Astragalus galactites (Fabaceae) - Xiaodong Ding; Chaopan Zhang; Yangqiong Gao; Zhanlin Bei; XingFu Yan (Mitochondrial DNA. Part B. Resources, 2021)
Astragalus galactites is a medicinal plant. The total plastome length of A. galactites is 126,117 bp. It contains a large single-copy region of 69,805 bp, two inverted repeat regions of 20,638 bp, and a small single-copy region of 15,036 bp. The cp genome contains 110 complete genes, including 75 protein-coding genes (75 PCGs), 4 ribosomal RNA genes (4 rRNAs), and 30 tRNA genes (30 tRNAs). The overall GC content of cp DNA is 33.9%, the corresponding values of the LSC, SSC, and IR regions are 33.0%, 30.4%, and 43.3% respectively. The phylogenetic tree shows that A. galactites has the closest relationship with A. laxmannii.